Pengembangan Video Pembelajaran Kalkulus Untuk Memahamkan Konsep - Sumargiyani Sumargiyani; Ardi Dwi Susandi; Muhammad Asrori Ainurrahman; Bidayatun Nafi'ah (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2021)
This research is motivated by the difficulty of students understanding the concept of integration techniques through bold learning, so that a concept understanding-based learning video is needed for flat area material. This study aims to develop learning videos and determine the validity and practicality of the videos produced. This type of research is in the form of ADDIE model development research (Analysis, Design, Development, Implementation, Evaluation). The research subjects were class B students, batch 2020, the Ahmad Dahlan University Mathematics Education study program. The results of the assessment from material experts obtained an average score of 4.77 with very good criteria, from material experts obtained an average score of 4.55 with very good criteria, and from student responses a score of 3.50 was obtained with good criteria so that it can be concluded that the video Integral calculus learning is valid and practical to use.Â Keywords: integral calculus, learning videos, trigonometric functions